2007
DOI: 10.1080/00365540701466173
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of infection control knowledge, attitude and practice among healthcare workers during the Hajj period of the Islamic year 1423 (2003)

Abstract: We assessed hospital infection control knowledge, attitude, and practice (KAP) of healthcare workers (HCWs) during the Hajj season of the Islamic y 1423 (2003). A self-administered structured questionnaire was used to collect the data. A total of 392 HCWs was studied, of whom 215 (54.8%) were nurses and 177 (45.2%) were doctors. 315 (80.4%) HCWs worked in hospitals, whereas 77 (19.6%) worked in primary healthcare centres. Of the 392 HCWs, 164 (41.8%) were from Makkah, and the remaining 228 (58.2%) were recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 6 publications
2
20
2
Order By: Relevance
“…This was better than rates reported from Russia (“overall scores were low”) [15] and the Philippines (misunderstanding of TB infection transmission despite high magnitude of TB in the general population) [16]. On the other hand, proportions of healthcare workers with “good” knowledge from Iraq (95.5%) [17], Saudi Arabia (81.8%), and Bangkok (85%) are higher than ours [18,19]. Explaining this knowledge difference is generally difficult; however, variations in the rates of “good” knowledge across countries could be attributed to the different settings and methodologies used by different studies.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This was better than rates reported from Russia (“overall scores were low”) [15] and the Philippines (misunderstanding of TB infection transmission despite high magnitude of TB in the general population) [16]. On the other hand, proportions of healthcare workers with “good” knowledge from Iraq (95.5%) [17], Saudi Arabia (81.8%), and Bangkok (85%) are higher than ours [18,19]. Explaining this knowledge difference is generally difficult; however, variations in the rates of “good” knowledge across countries could be attributed to the different settings and methodologies used by different studies.…”
Section: Discussioncontrasting
confidence: 70%
“…This is much lower than what is observed from Bangkok [18]. Mask usage is reported by only 21.1% of the respondents, which is much lower than that reported from Bangkok [18] and South Africa [21]. The difference in these findings may be attributed to the unavailability of the masks.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…There are numerous studies describing the HCAI knowledge, attitudes, and practice of physicians and nurses practicing in various disciplines, with conflicting findings [4], [20], [21]. Our knowledge assessment showed nurses were generally better than physicians particularly in hand hygiene, perhaps because nursing job is more patient-oriented and compliance demanding.…”
Section: Discussionmentioning
confidence: 66%
“…[23243031] In a related study, Bamigboye and Adesanya[32] observed a higher level of knowledge among nursing students 77%, compared to medical students, 61%, with only 18.9% of the students claiming that universal precautions featured during their classroom sessions. Therefore, they concluded that the exclusion of such important topics from the medical education curriculum as the possible reason for the poor practice of universal precaution observed among medical student in their study.…”
Section: Discussionmentioning
confidence: 99%